Understanding values of the Malay cultural responsive landscape through informational processing model - Ismail, Nor Atiah; Utaberta, Nangkula; Ariffin, Noor Fazamimah; Ismail, Sumarni; Mohd Yunos, Mohd Yazid (American-Eurasian Network for Scientific Information, 2015)
Background: Landscape preference study is another field of environmental research that has the relevancy in understanding the Malay culturally responsive landscape. Objectives: There are several theories that have been developed in accordance to this research, for instance the Informational Processing Model. A case study is conducted at Kampung Parit Sayang of Benut, Johor. These cognitive studies examine the physical character of the setting by the help of landscape photograph of particular interest. Results: The Informational Processing Model focuses on the aesthetic preference of human being intheir landscape setting. Conclusion: Based on their comprehensive studies, it is concluded that the four factors; coherence, legibility, complexity and mystery are the most important factors that determine human preferences to the environment.